Fingerprint image enhancement using median sigmoid filter - Abdul Hamid, Ainul Azura (Penerbit UTM Press, 2015)
Quality of fingerprint image is most essential to ensure good performance of minutiae extraction result since it depends heavily on the quality of fingerprint images. Fingerprint image with noise usually will produce spurious minutiae. In this paper, new combination filter called Median Sigmoid (MS) filter is introduced to remove the unwanted noise created during the acquisition process and hence increasing the accuracy of minutiae extraction result. The result shows that MS filter is an effective filter in enhancing the quality of a noisy image.